Strategic Resource Management for Sustainability Performance: Sequential Mediation of Farmer Empowerment and ESG Practices in Agriculture - Vera Sylvia Saragi Sitio; Meidiana Purnamasari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The agricultural sector faces growing pressure to achieve food security while improving economic, social, and environmental sustainability, particularly in developing countries where smallholder farmers face resource, technological, and institutional constraints. This study examines the effects of resource management strategies, farmer empowerment, and Environmental, Social, and Governance (ESG) practices on sustainability performance, including the sequential mediating roles of farmer empowerment and ESG practices, and identifies strategic priorities using Importance–Performance Map Analysis (IPMA). Using an explanatory quantitative approach, data were collected through a cross-sectional survey of 138 agricultural actors in Indonesia’s food crop and horticultural sectors using purposive sampling. We analysed the data using PLS-SEM in SmartPLS 4.0 and IPMA. The findings show that resource management strategies, farmer empowerment, and ESG practices significantly improve sustainability performance. Farmer empowerment and ESG practices partially mediate the relationship between resource management and sustainability outcomes, including sequential mediation. IPMA identifies resource management strategy as the most critical factor. Theoretically, the study extends the Resource-Based View and capability approach by demonstrating that sustainability depends not only on resource availability but also on how resources are transformed through empowerment and sustainable governance. Practically, it highlights the need to strengthen resource management, farmer capacity, and ESG integration among agricultural actors, farmer organisations, and agribusiness communities.Contribution to Sustainable Development Goals (SDGs):SDG 2:  Zero HungerSDG 8:  Decent Work and Economic GrowthSDG 12:  Responsible Consumption and ProductionSDG 13:  Climate Action